VR Health Experience: A Virtual Space for Arts and Psychomotor Therapy - Haeyen, Suzanne; Jans, Nathalie; Glas, Marleen; Kolijn, Joep (Frontiers in Psychology, 2021)
Introduction: Mental health and well-being are under pressure because of the corona pandemic. Arts and psychomotor therapists said that they had almost no experience with working online, but despite the fact that they felt incapable, they were positive towards it. Method: This qualitative action research was aimed at how arts and psychomotor therapists can become more skilled in offering online arts and psychomotor therapy and how they can methodically enlist the VR Health Experience (a virtual arts and psychomotor therapy space) in therapy. It is envisaged that the arts and psychomotor therapist could be telepresent in order to offer arts and psychomotor therapy remotely. In online training that made use of the Lean Startup Method, participants (n = 5) integrated their working knowledge with the VR Health Experience. The interventions were immediately tested by the participants and in practice. Participants were interviewed retrospectively and their experiences were thematically analysed. Results: The VR Health Experience came forward as an innovative addition to the usual arts and psychomotor therapy. Often, clients were encouraged to play and experiment, and the VR world offered several options. The VR Health Experience lowered the threshold, expanded the training areas and held a great attraction for play. Discussion: This project offered an innovative quality boost for arts and psychomotor therapy. Arts and psychomotor therapy have proven to be possible remotely via telepresence of the therapist. The therapist is present together with the client in the VR Health Experience, the virtual arts and psychomotor therapy space, where connectedness can be felt and new experiences can be gained. VR also offers further possibilities in arts and psychomotor therapy.